Cognitive style, academic self-concepts, and creativity as predictors of achievements in science and mathematics. - Suan, Yoong (1994)

(untitled)
Three broad categories of psychological-aptitude constructs, namely, intellectual abilities, cognitive/learning styles, and academic motivation/personality characteristics, are generally considered as critical predictors of educational performance.